German wage moderation and European imbalances: Feeding the global VAR with theory - Timo Bettendorf; Miguel A. León-Ledesma (Deutsche Bundesbank, 2015)
German labor market reforms in the 1990s and 2000s are generally believed to have driven the large increase in the dispersion of current account balances in the Euro Area. We investigate this hypothesis quantitatively. We develop an open economy New Keynesian model with search and matching frictions from which we derive robust sign restrictions for a wage bargaining shock. We then impose these restrictions on a Global VAR consisting of Germany and 8 EMU countries to identify a wage bargaining shock in Germany. Our results show that, although the German current account was significantly affected by wage bargaining shocks, their contribution to European current account imbalances was negligible. We conclude that the reduction in bargaining power of German unions after labor market reforms cannot be the lone driver of European imbalances.
Keywords: F10; F32; F41; 330; european imbalances; German wage moderation; DSGE; Global VAR; sign restrictions